2015
DOI: 10.31018/jans.v7i1.611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cultivars and seed size on field performance of potato micro-tubers in North Eastern Himalayan region in India

Abstract: The present study was carried out at Central Potato Research Station, Shillong during 2013 and 2014 to assess the growth and yield performance of three grades of in-vitro produced micro-tubers viz. >8 mm, 4-8 mm and <4 mm of two potato (Solanum tuberosum) cultivars namely Kufri Girdhari and Kufri Megha under field planting conditions. The experiment was laid out in a randomised block design with four replications using a common spacing of 50 × 20 cm. The larger grade micro-tubers generally exhibited better phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 8 publications
4
6
0
Order By: Relevance
“…Significantly higher stem/plant was recorded >8mm size microtubers (1.7) followed by >6-8mm size (1.2) over >4mm size microtubers (1.1) table 1. Present findings are also in agreement with Srivastava et al (2015) who reported that larger sized micro-tubers (>8 mm and 4-8 mm) did not exhibited significant (α = 5%) difference in terms of stems/plant but were superior to those in the smallest size microtuber (<4 mm). Number of compound leaves/plant at 50 days after planting were significantly higher at 5% level in 1ppm gibberllic acid+1% thiourea (12.1) followed by 1ppm gibberllic acid (11.9) over water control (8.8).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Significantly higher stem/plant was recorded >8mm size microtubers (1.7) followed by >6-8mm size (1.2) over >4mm size microtubers (1.1) table 1. Present findings are also in agreement with Srivastava et al (2015) who reported that larger sized micro-tubers (>8 mm and 4-8 mm) did not exhibited significant (α = 5%) difference in terms of stems/plant but were superior to those in the smallest size microtuber (<4 mm). Number of compound leaves/plant at 50 days after planting were significantly higher at 5% level in 1ppm gibberllic acid+1% thiourea (12.1) followed by 1ppm gibberllic acid (11.9) over water control (8.8).…”
Section: Resultssupporting
confidence: 93%
“…There was increase in plant height with increase in the GA 3 doses from 0 to 160 ppm in variety Morphona (Shekari et al, 2010) >8mm size microtubers (59.7 cm) at 75 days after planting. Increase in micro-tuber size from <4mm to >8mm size there was a corresponding increase in plant height when reported after 60 days after planting (Srivastava et al, 2015). This confirms the present findings of increase in plant height with increase in tuber size.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Microtubers are more vigorous, easy to store and easier to handle comparing with in vitro plantlets Coleman, 1988 andMcCown& Joyce, 1991). Recently, many researches compared the performance of microtubers with traditional potato seed tubers and minitubers (Struik & Lommen, 1999, Wróbel, 2015and Srivastava, 2015. Furthermore, microtubers is used in potato seed production in many countries they improved self-sufficiency, reduce number of field generation and reduce disease frequency in the final product (Donnelly et al, 2003).…”
Section: Introductionmentioning
confidence: 99%